The mentoring in practice-oriented pedagogical education: based on the experience of «Teacher training college in Sevastopol named after P.K. Menkov» - Danilchenko S. L. (Humanitarian, 2018)
the future specialist needs to form general and professional competencies in the learning process, including the system of secondary professional education. The system of dual (practice-oriented) learning is actively developing. The process of practical training is managed under the guidance of college teachers. The role of pedagogical workers of educational institutions on the basis of which the students obtain professional skill is limited by supervision.
Keywords: образование; студенты; практика; сопровождение; условия; наставничество; колледж; students; education; mentoring; институт наставничества; mentoring in education; activity of pedagogical employees of the college; практикоориентированное педагогическое образование; проблемы наставничества; дуальное профессиональное образование; деятельность педагогических работников; педагогический колледж; the practice; practice-oriented teacher education; mentoring problems; terms; dual professional education; pedagogical college